2013
DOI: 10.1097/brs.0b013e3182a7f449
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Radiographical Alignment

Abstract: Cervical deformity correction should take on a comprehensive approach in assessing global cervical-pelvic relationships and the radiographical parameters that effect health-related quality of life scores are not well-defined. Cervical alignment may be important in assessment and treatment of cervical myelopathy. Future work should concentrate on correlation of cervical alignment parameters to disability scores and myelopathy outcomes. SUMMARY STATEMENTS: STATEMENT 1: Cervical sagittal alignment (cervical SVA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
224
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 449 publications
(236 citation statements)
references
References 64 publications
7
224
1
4
Order By: Relevance
“…This study also noted predictable improvements in pelvic parameters. A mild loss of LL is correlated with a hypokyphosis or a lordosis of the thoracic region, whereas a more significant loss of LL is correlated with pelvic retroversion (increased PT) as a compensatory mechanism [2]. This study found a decrease in pelvic retroversion to within the reference normal pelvic values following improvement in lumbar alignment.…”
Section: Discussionsupporting
confidence: 47%
See 4 more Smart Citations
“…This study also noted predictable improvements in pelvic parameters. A mild loss of LL is correlated with a hypokyphosis or a lordosis of the thoracic region, whereas a more significant loss of LL is correlated with pelvic retroversion (increased PT) as a compensatory mechanism [2]. This study found a decrease in pelvic retroversion to within the reference normal pelvic values following improvement in lumbar alignment.…”
Section: Discussionsupporting
confidence: 47%
“…Reference normal values for spinopelvic parameters were obtained from a cross-sectional study by Vialle et al [21] of 300 asymptomatic volunteers. Reference normal values for cervical parameters were obtained from Ames et al [2], which was adapted from a study by Hardacker et al [22], in addition to a cross-sectional study of 106 healthy volunteers by Le Huec et al [23]. A value was considered ''normative'' if within one standard deviation from the mean of reference normative values.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations